RIES AND CHICXULUB: IMPACT CRATERS ON EARTH PROVIDE INSIGHTS FOR MARTIAN EJECTA BLANKETS - Kenkmann T.; Schönian F. (My University, 2006)
Terrestrial impact structures provide field evidence for cratering processes on planetary bodies that have an atmosphere and volatiles in the target rocks. Here we discuss two examples that may yield implications for Martian craters: 1. Recent field analysis of the Ries crater has revealed the existence of subhorizontal shear planes (detachments) in the periphery of the crater beneath the ejecta blanket at 0.9-1.8 crater radii distance. Their formation and associated radial outward shearing was caused by weak spallation and subsequent dragging during deposition of the ejecta curtain. Both processes are enhanced in rheologically layered targets and in the presence of fluids. Detachment faulting may also occur in the periphery of Martian impacts and could be responsible for the formation of lobe-parallel ridges and furrows in the inner layer of double-layer and multiple-layer ejecta craters. 2. The ejecta blanket of the Chicxul ub crater was identified on the southeastern Yucatán Peninsula at distances of 3.0-5.0 crater radii from the impact center. Abundance of glide planes within the ejecta and particle abrasion both rise with crater distance, which implies a ground-hugging, erosive, and cohesive secondary ejecta flow. Systematic measurement of motion indicators revealed that the flow was deviated by a preexisting karst relief. In analogy with Martian fluidized ejecta blankets, it is suggested that the large runout was related to subsurface volatiles and the presence of basal glide planes, and was influenced by eroded bedrock lithologies. It is proposed that ramparts may result from enhanced shear localization and a stacking of ejecta material along internal glide planes at decreasing flow rates when the flow begins to freeze below a certain yield stress. © The Meteoritical Society, 2006.